Complete Genome Sequence of the Newly Developed Lactobacillus acidophilus Strain With Improved Thermal Adaptability - Jeon, Soomin; Kim, Hyaekang; Choi, Youngseok; Cho, Seoae; Seo, Minseok; Kim, Heebal (Frontiers in Microbiology, 2021)
Lactobacillus acidophilus L. acidophilus ) i s a representative probiotics and is 28 widely used in many industrial products for its beneficial effects on human and 29 animal health. This bacteri um expose s to harsh environment s such as high 30 temperature s for manufacturing industrial products, but cell yield und er high 31 temperature s is relatively low. To resolve this issue, we developed a new L. 32 acidophilus strain with improved heat resistance while retaining the existing 33 beneficial properties through the adaptive laboratory evolution (ALE) method. The 34 newly devel oped strain, L. acidophilus EG008, has improved the existing limit of 35 thermal resistance from 65˚C to 75˚C. Furthermore, we performed whole genome 36 sequencing and comparative genome analysis of w ild type and EG008 strains to 37 unravel the molecular mechanism of improved heat resistance. Interestingly, only 38 two single nucleotide polymorphisms (SNPs) were different compared to the L. 39 acidophilus wild type. We identified that one of these SNPs is a non synonymous 40 SNP capable of altering the structure of MurD prot ein through the 4 3 5 th amino acid 41 change from serine to threonine. We believe that these results will directly 42 contribute to an industrial field where L. acidophilus is applied. In addition, these 43 results make a step forward in understanding the molecular m echanisms of lactic 44 acid bacteria evolution under extreme conditions. 45